Stationary-Mixing Field-Programmable Pin-Constrained Digital Microfluidic Biochip. (July 2018) - Abdoli, Alireza; Brisk, Philip
Abstract: This paper introduces a Field Programmable Pin-Constrained (FPPC) architecture for a Digital Microfluidic Biochip (DMFB) that integrates a new stationary hydrodynamic mixing technology. Compared to the traditional rotation-based mixing, stationary mixing is faster, requires fewer electrodes, and limits residue production and the likelihood of biofouling. Although the stationary mixing principle has been established, programmable DMFB architectures that feature stationary mixing have not been investigated or evaluated. Simulation results show that the Stationary Mixing FPPC (SM-FPPC) architecture introduced here outperforms existing Direct Addressing (DA) and FPPC DMFBs that employ traditional rotation-based mixing. An analysis based on a commercially available Printed Circuit Board (PCB) cost calculator demonstrates a 31% reduction in cost compared to the lowest cost PCB reported in prior literature.